2013
DOI: 10.1111/ijn.12152
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the cultural problems encountered during caregiving by the nurses working in two different regions of Turkey

Abstract: The aim of this study was to identify the cultural problems encountered during caregiving by the nurses working in two university hospitals located in western and eastern Turkey. This descriptive, comparative study was conducted between July 2008 and October 2009 with 338 nurses who volunteered to take part in the study. The study data were collected using an individual description questionnaire consisting of 10 questions and another questionnaire consisting of 14 questions to identify the cultural problems en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Even people who speaking same language may have problems in terms of perception; thus, it is natural that those who are speaking different languages will have more problems understanding each other (Parlar Kılıç et al. ; Sagar ). Lack of cultural awareness and difficulty with communication constitute barriers to understanding between nurses and patients from different cultures (Stimpson & Martin ).…”
Section: Discussionmentioning
confidence: 99%
“…Even people who speaking same language may have problems in terms of perception; thus, it is natural that those who are speaking different languages will have more problems understanding each other (Parlar Kılıç et al. ; Sagar ). Lack of cultural awareness and difficulty with communication constitute barriers to understanding between nurses and patients from different cultures (Stimpson & Martin ).…”
Section: Discussionmentioning
confidence: 99%
“…Discussion: According to the findings of the research, a statistically significant relationship was determined between the mean of "Empathy Tendency Scale" and "Intercultural Sensitivity Scale" (r = 0.228, p <0.05). In the studies of EgelioğluCetişli et al (2016), Parlar et al (2014, Dikmen et al (2016), andKurtüncü et al (2018), it was found that the relationship between the averages of the "Empathy Tendency Scale" and the averages of the "Intercultural Sensitivity" was found a positive relationship. These findings are in same with this study.…”
Section: Extended Abstractmentioning
confidence: 97%